Selection of Pepper Varities Suitable for Cultivation in Greenhouses with Unheated Film - A.J. Shokirov; D. M. Yakubova; Sh.Sh. Sharipova; J. Kholmamatov (Research Parks Publishing LLC, 2021)
The article reveals the importance of sweet pepper, the total yield and crop yield of productivity that grown in the world as well as in our country. Here is also highlighted the selection of sweet pepper varieties, the yield and quality as well as their resistance to fusarium wilt for growing in unheated greenhouses